Medication use in infants with severe bronchopulmonary dysplasia admitted to United States children’s hospitals - Bamat, Nicolas A.; Kirpalani, Haresh; Feudtner, Chris; Jensen, Erik A.; Laughon, Matthew M.; Zhang, Huayan; Monk, Heather M.; Passarella, Molly; Lorch, Scott A. (Journal of perinatology, 2019)
Objective To identify the number of cumulative medication exposures and most frequently used medications in infants with severe BPD. Study design We performed a retrospective cohort study in infants with severe BPD admitted to United States children’s hospitals. We measured cumulative medication exposures in individual subjects and between-center variation after adjustment for infant characteristics. We then identified the specific medications and therapeutic classes with the highest rates of use. Results In 3252 subjects across 43 hospitals, we identified a median (interquartile range) of 30 (17–45) cumulative medication exposures per infant. The adjusted mean number of medication exposures varied between centers ( p < 0.0001), with a range of 22–50. Diuretics and furosemide were the most frequently prescribed therapeutic class and specific medication for the management of severe BPD. Conclusions Infants with severe BPD are exposed to alarming number of medications of unclear efficacy and safety, with marked variation between center.